Pengaruh Kepribadian, Gaya Hidup dan Kompensasi Terhadap Kinerja ASN Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Tulungagung - Istiani Istiani; Edy Swasono (Universitas Islam Kadiri, 2023)
The success of development in the Government, Civil Servants (ASN) plays determining role factor. The ability to have an intention, reasons, and rationality make these elements control the other factors such as Human Resources, Capital, Infrastructure, Social, and etc. Therefore, ASN is required to have integrity and professionalism that will have a positive impact on the achievement of performance. This study aims to analyze the influence of personality, lifestyle, and compensation on the performance of ASN employees at the Regional Financial and Asset Management Agency of Tulungagung Regency. The research object was 59 Civil Servants at the Regional Financial and Asset Management Agency of Tulungagung Regency. Simultaneously we found a positive and significant influence of Personality, Lifestyle, and Compensation factors on Employee Performance. When partially testing, we also found that these factors had the same result. The study concluded that ASN who have a high level of creativity and curiosity, have an interest and a positive outlook on work, and receive appropriate allowances and facilities have an impact on performance achievement.